(untitled) (Experimental biology, 2015)
In the study, the gene COL4A5 was genotyped by direct sequencing of the family with X-linked Alport syndrome. Based on the results of genotyping of both members of the family identified previously described mutation ekzone2204G 25> A, due to the replacement of glycine with glutamic acid in position 735. They are the carriers of the heterozygous mutation allele B25 exon (Gly735Glu). As a result, it can be concluded the mutation Gly735Glu, is pathogenic and associated with juvenile type of hereditary nephritis, which is characterized by early development of chronic renal failure (16 years).